Wavelet analysis based VTEC variability over mid-latitude region Sukkur, Pakistan and its comparison with IRI models during 2019-2020 - Rasim Shahzad; Amna Hafeez; Jose Francisco De Oliveira-Junior; Arslan Ahmed; Punyawi Jamjareegulgarn; Najam Abbas Naqvi (My University, 2022)
The Total Electron Content (TEC) from the Sukkur GPS station is studied during the final phase of the solar cycle 24 and the initial phase of solar cycle 25 (2019-2020). TEC comparisons are made with three international reference ionospheric models: IRI-2007, IRI-2012 and IRI-2016. The finding of the study indicates that IRI-2016 is better than IRI-2007 and IRI-2012 in monthly values using wavelet transformation. Moreover, the seasonal variations between observed and modelled VTEC were observed maximum during the spring season. Similarly, the IRI-2016 exhibited maximum correlation (i.e., r > 0.8) as compared to the other two models for both solar cycle phases. This study also includes a cross-correlation of GPS-VTEC with several storm indices (Kp, Dst, Ap) via wavelet transformation. In this paper, the wavelet spectrum is analysed for two-year data (2019-2020) to visualize the impact of geomagnetic storm indices on VTEC. Storms of different intensities during 2019-2020 solar activity were also analysed, where maximum correlation from wavelet transformation between GPS VTEC and geomagnetic indices was recorded during the initial solar phase of cycle 25. These kinds of studies assist to correct the measured GPS VTEC and help to improve predicted VTEC over mid-latitude regions.
Keywords: Solar cycle 24; International Reference Ionosphere; Earthquake Detection and Analysis